Study of Determining the Value of Passenger Cars Equivalence (PCE) on Divided Urban Roads - Mukti, Elsa Tri; Irwandi, Irwandi; A.S., M. Zulfikar; H., M. Naufal (Jurnal Teknik Sipil, 2025)
Passenger Car Equivalence (PCE) is a crucial parameter for assessing the contribution of various vehicle types to traffic density on a road segment. Multiple factors, including road type, geometric conditions, and traffic volume, influence PCE values. Each road segment has unique traffic characteristics and geometric conditions, making previously established PCE values potentially outdated. The Indonesian Highway Capacity Manual (PKJI) 2023 provides PCE values as a reference for planning; however, their relevance needs to be evaluated in light of the increasing number of vehicles and changing traffic operational patterns, particularly in urban areas. This study aims to analyze the PCE values of motorcycles (MC) and medium vehicles (MV) on an urban road with a two-way, two-lane, and four-lane divided configuration using the Time Headway method and to compare the results with the PCE values specified in PKJI 2023. The research was conducted on Tanjung Pura Street, Pontianak, yielding PCE values of 0,281 for MC and 1,175 for MV. These values represent differences of 12,51% for motorcycles and 2,06% for medium vehicles compared to PKJI 2023. These findings highlight the need for an evaluation of PCE values based on empirical data to support more accurate road capacity planning and traffic management.